CONCEPT MASTERY AND SCIENTIFIC LITERACY CAPABILITY OF SENIOR HIGH SCHOOL OF 1 KUDUS STUDENTS - Prabowo, Herwidhi Tri; Rusilowati, Ani; Wahyuni, Siti (Universitas Negeri Semarang, 2018)
The purpose of this study is to identify concept mastery and scientific literacy capability of senior high school students. This study used quantitative-qualitative mix method. This study was conducted at senior high school students of 1 Kudus. The subjects of this study were 12th grade student who have received all the subject matter of physics. The instruments of this study were concept-based and scientific literacy-based multiple choice test accompanied by the reason. The level of concept mastery and scientific literacy capability of students was analyzed through the appropriateness of the choice of answers with the reasons. The results shows that the lowest level of concept mastery and scientific literacy capability of senior high school students is item Graduate Competence Standards (GCS) 3 about heat and thermodynamics. From the results can be conclude that concept mastery influences the students' scientific literacy capability